The Effect of Customer Relationship Management (CRM) To Customers’ Loyalty and Customers’ Satisfaction as Mediator Variables - Fikriya Emaluta; Isnalita; Noorlailie Soewarno (Jurnal AKSI (Akuntansi dan Sistem Informasi), 2019)
This research aims at exploring the effect of customer relationship management (CRM) which based of several indicators, such as information and data, process, technology, human resource; focused on customers’ loyalty and customers’ satisfaction as the mediator variable of PT Gojek Indonesia. The analysis uses structural equation modelling (SEM) with warp PLS version 5.00 program to examine the hypothesis. There are 216 respondents in this research. The respondents are the Gojek Indonesia’s customers. The result of the research shows that there positive effect and significance between the CRM of Gojek Indonesia’s service provided and costumers’ satisfaction and loyalty. It also indicates that the result of the research is consistent with the previous CRM research findings and the findings of the current research, where the CRM of Gojek Indonesia’s service gives indirect positive effect to the costumers’ loyalty through costumers’ satisfaction that shows supportive mediator relation between CRM, customers’ satisfaction, and customers’ loyalty.